Socialization of infant blue monkeys (Cercopithecus mitis stuhlmanni): Allomaternal interactions and sex differences - Förster, Steffen; Cords, Marina (Behaviour, 2005)
AbstractAn important part of the ontogeny of social mammals is the establishment of social relationships with non-mothers. Mothers may influence this socialization process, but other factors like the number and kind of potential partners available may also be important. In matrilineal societies, variation in allomaternal social experience is also likely to differ for males and females, relating to differences in their respective life histories. We investigated differences in non-maternal social relationships of 12 infant blue monkeys (Cercopithecus mitis stuhlmanni) in their first six months of life in a wild population. Based on previous findings that blue monkey infants develop spatial independence from their mothers at a relatively early age, we expected that infants would also socialize with non-maternal group members early in life. As possible determinants of variation in infant socialization, we evaluated the effects of age, sex, group composition, and timing of birth relative to the birth season. Allomaternal social relationships of infants differed between social groups, largely but not exclusively in response to differences in group composition. Adjusting for these group differences, we found that infants generally avoided spatial proximity to non-maternal adult females, whereas they associated more than expected by chance with other infants and large juvenile females, when away from their mothers. Close spatial association with other adult females and small juveniles increased when infants were near their mothers. Association with other infants decreased with proximity to the mother, apparently because peer playgroups led infants away from their mothers. Infants were spatially well integrated into the core of the group, associating with most available adult and large juvenile partners. Male infants spent more time in social play than females, and engaged in more rough-and-tumble play bouts, and in bouts of longer duration, than females. Large juvenile females regularly took care of infants, whereas adult females rarely acted as caretakers. There were no sex differences in behavior directed towards infants by non-mothers, but female infants associated more than male infants with adult females when away from their mothers. Although sex differences in social play correspond to similar differences in the importance of fighting skills for adults, alternative explanations for the observed pattern remain plausible. Our data support the hypothesis that allomaternal care functions as infant handling practice for nulliparous females. The relatively rapid social development we observed in our subjects contrasts with the generally slow life history of the species and suggests that developmental rates during infancy and juvenility are promoted and constrained by different factors.